The Influence of Video-Based Nutrition Education on Knowledge of Pregnancy Nutrition in Pregnant Women in Sinar Pasemah Village - Wayan Nilawati; Riska Ismawati; Dian Monalisa (Journal of Educational Innovation and Public Health, 2025)
The percentage of pregnant women chronic energy deficiency in Indonesia is 9.7%, in Lampung Province it is 13.62%. The prevalence of chronic energy deficiency risk for pregnant women in Bandar Lampung is 17.36% and for non-pregnant women is 17.02%. One of the causes of malnutrition in pregnant women is the lack of knowledge of mothers about nutritious foods during pregnancy. The purpose of the study is to determine the influence of video-based nutrition education on pregnant women's knowledge about pregnant women's nutrition in Sinar Pasemah Village. Experimental quasi research design designed by Two Group Pre-Post Test with Control Group Design. The population is 46 pregnant women. A total of 46 samples were selected with a total sampling, consisting of 23 respondents from the video group and 23 respondents from the lecture group. Univariate data analysis with frequency distribution tables, Bivariate analysis with Wilcoxon test and Mann Whitney test. The average knowledge of pregnancy nutrition before video-based education was 63.26 and the average knowledge of pregnancy nutrition after video-based education was 78.48 with ap value of 0.000. Meanwhile, the average knowledge of pregnancy nutrition before lecture education was 63.04 and the average knowledge of pregnancy nutrition after lecture education was 74.57 with ap value of 0.000. The results of the Mann Whitney test were obtained 0.020. There is an influence of video-based education and lecture education on pregnancy nutrition knowledge and there is a difference in the influence of video education and lecture education on pregnancy nutrition knowledge in pregnant women in Sinar Pasemah village.